Pharmacoeconomic analysis of oral and injectable proton pump inhibitors available in India - Pradnya Deolekar; Kavitha Vivek Dongerkery; Jyoti Sonawane; Pramila Yadav; Azra Naseem (Journal of Applied Pharmaceutical Research, 2023)
Introduction: Proton pump inhibitors (PPIs) effectively suppress acid secretion and play an important role a lot of gastrointestinal disorders. PPIs are generally used long term by the patients. This can cause an increase in patient cost and subsequent decrease in adherence to the prescription. Hence, this study was done to assess the cost variation of PPIs. Methods: The cost of different brands of commonly used PPIs (10 capsules/tablets for oral drugs and one ampoule/vial for injectable drugs) was tabulated by referring to the “Monthly Index of Medical Specialties” October – December 2021, and 1mg online pharmacy. The cost ratio and percentage cost variation for various brands of a particular strength and dosage form was calculated and compared. Cost ratio >2 and cost variation >100% was considered significant. Results: The results showed a huge variation in costs of different brands with the highest being Rabeprazole 20mg (Cost ratio-16.4, Percentage cost variation-1540%) in oral formulation and Rabeprazole 20mg (11.9, 1090%) in the injectable formulation. Among oral drugs, Omeprazole 40mg has the lowest cost ratio and percentage cost variation (1.60, 60.34%) and Pantoprazole 40mg (1.51, 51.16%) in case of injectable formulations. Conclusion: There is a wide variation in the prices of PPIs available in the market. Huge demand for the commonly orally prescribed drugs like Omeprazole 20mg and Pantoprazole 40mg could be the reason for the high cost. Among injectable preparations, Pantoprazole 40mg is the most commonly prescribed but it has an acceptable cost ratio which is a positive sign.